MULTIVARIATE ANALYSIS OF COMMODITY AVAILABILITY OF STAPLE FOODS USING COMPLETE LINKAGE HIERARCHICAL CLUSTERING METHOD - Sitio, Arjon; Sinaga, Anita Sindar; Haikal, Akhyar; Dewi, Sumitra (LPPM Nusa Mandiri, 2022)
The government directly supervises 11 basic food commodities. The system of interplay between the price of goods and the availability of staple food directly has an impact on the high price of food at certain times. It is necessary to classify the food that is most needed by the community on big holidays in Indonesia so that it can be a reference for the government in preparing market needs in the coming year. In this study, the grouping of staple food availability was based on hierarchical cluster analysis with complete linkage method. The availability of food commodities in the discussion of this research is sourced from production materials and daily prices for meat, eggs, cooking oil and rice commodities. Cluster interpretation results in cluster 1 indicating Fulfilled Availability of 88-89%, Cluster 2 showing Sufficient Commodity Availability of 90-93% and Cluster 3 showing Availability of Rare Commodities of 87%. The three clusters formed are depicted in the form of a dendogram as a visualization of the relationship between food availability groupings.